Usage of Heat Treatment and Modified Atmosphere Packaging to Maintain Fruit Firmness of Fresh Cut Cavendish Banana (Musa cavendishii) - Utama, Nafi Ananda (Universitas Muhammadiyah Yogyakarta, 2020)
Increasingly healthy lifestyles and advances in technology make people tend to prefer consuming fresh-cut fruits. Modified Atmosphere Packaging (MAP) contributes to extending shelf life and improving postharvest product quality. This study was aimed to determine the effects of argon-based MAP combined with heat treatment on the quality of the fresh-cut cavendish. There were four treatments examined, consisting of the combination of MAP with 73.70 % argon gas and heat treatment at 40 °C for 5 minutes (P1), heat treatment at 40 °C for five minutes (P2), MAP with 73.70 % argon gas (P3), and without treatment (P4). Each treatment consisted of three replications, and all experimental units were stored in a storage area at a temperature of 10 °C. The variables of fruit hardness, total titratable acidity, reducing sugar content, and total phenolic compounds were observed at 0, 2, 4, 6, 8, and 10 days of storage. The results of the study showed that MAP and heat treatment could maintain freshness and slow down the degradation of fresh-cut cavendish quality. The combination of MAP treatment with 73.70 % argon gas and heat treatment at 40 °C for five minutes can slow down the degradation of fresh-cut cavendish quality and suppress the total titratable acidity formation until the end of the storage period (ten days).